Isocinétisme et cheville : bilans, rééducation et prévention en traumatologie - Fourchet, F. (Movement & Sport Sciences - Science & Motricité, 2014)
The use of isokinetic dynamometers has become very common at the ankle joint level in prevention, evaluation and rehabilitation; of course without replacing the traditional assessment and treatment techniques. Protocols exist for two movements at the ankle-foot region: plantar/dorsal flexion and inversion/eversion. For a better understanding and an effective use of isokinetic tool at the ankle, it is essential to master the common terms usually associated with isokinetic such as peak torque, work or agonist/antagonist ratio. For each of the different possible movements the subject positions are described (in particular, varying the angle of knee flexion) and several protocols (in relation with the different brands of machines and specific evaluation criteria) are reported in the literature. The major parameters such as speed, number of repetitions or recovery time are recalled. Specific indications exist for isokinetic use at the ankle in prevention and treatment. The treatment of triceps and Achilles damaged structures in eccentric mode is the major indication for the use of isokinetic in dorsal/plantar flexion. Prevention and rehabilitation of ankle sprains and ankle instability are major indications to use this tool in inversion/eversion. It is worth noting as well that isokinetic can be applied among adolescent athletes and that assessments of muscle fatigue is of great interest in preventing overuse injuries related to intensive sport practice.